Revolutionizing Language Learning: The Role of Artificial Intelligence in Mastering English - Bakhtiyorova Durdona Ikhtiyorovna (Scientific Trends, 2025)
This article investigates the impact of artificial intelligence (AI) on the transformation of English language learning. It explores how AI-driven tools such as Duolingo, Grammarly, and ELSA Speak are altering the way learners engage with English. Through personalized learning pathways, immediate feedback, and advanced speech recognition features, these tools have enhanced the accessibility, efficiency, and engagement of language acquisition. The article also addresses the challenges and ethical issues related to the use of AI in education, including concerns about data privacy and the continued role of human educators.
Keywords: Artificial Intelligence (AI), English Language Learning, AI-driven Tools, Duolingo, ELSA Speak, Personalized Learning, Immediate Feedback, Speech Recognition, Language Acquisition, Accessibility, Efficiency, Engagement, Educational Technology, Ethical Issues, Data Privacy, Human Educators, Challenges in Education, Digital Learning, AI in Education.